The Influence of Work Environment and Job Embeddedness on Organizational Citizenship Behavior in Digital Media Businesses - Syahida Aulia Sakinah; Muhardi Muhardi; Hendrati Dwi Mulyaningsih (Research Synergy Foundation, 2023)
This research aims to find out (1) the conditions of the work environment, (2) job embeddedness, (3) organizational citizenship behavior, (4) the influence of work environment on organizational citizenship behavior, (5) the influence of job embeddedness on organizational citizenship behavior; (6) and the collective influence of work environment and job embeddedness on organizational citizenship behavior at PT Ayo Media Network. The research methodology employed is a rigorous descriptive verification approach. Data gathering methods encompass a comprehensive spectrum, including administering surveys, conducting interviews, and meticulous documentation retrieval, all closely aligned with the research objectives. The research population encompasses the entire workforce of PT Ayo Media Network, ensuring a holistic perspective. Employing a saturated sampling technique with a carefully selected sample size of 95 respondents, the research maintains a robust statistical foundation. Furthermore, data analysis leverages the power of multiple linear regression analysis. The research findings unveil the following insights: (1) The work environment at Ayo Media Network garners an overall positive assessment, reflecting its quality; (2) Similarly, the evaluation of job embeddedness at PT Ayo Media Network is favorably rated overall; (3) The overarching perspective on organizational citizenship behavior at PT Ayo Media Network is characterized by a positive outlook; (4) The research substantiates that the work environment significantly shapes organizational citizenship behavior within PT Ayo Media Network; (5) In contrast, job embeddedness emerges as a factor with no discernible impact on organizational citizenship behavior within the organization; (6) Notably, when the combined influence of the work environment and job embeddedness is considered, it becomes evident that they collectively wield a significant effect on organizational citizenship behavior at PT Ayo Media Network. In summary, this research underscores the relatively favorable nature of the work environment, job embeddedness, and organizational citizenship behavior at PT Ayo Media Network, with a key revelation being that it is primarily the work environment that exerts influence on organizational citizenship behavior within the organization.